Trawl exposure and protection of seabed fauna at large spatial scales. Issue 11 (6th September 2017) - Mazor, Tessa K.; Pitcher, C. Roland; Ellis, Nick; Rochester, Wayne; Jennings, Simon; Hiddink, Jan Geert; McConnaughey, Robert A.; Kaiser, Michel J.; Parma, Ana M.; Suuronen, Petri; Kangas, Mervi; Hilborn, Ray
Abstract: Aim: Trawling is the most widespread direct human disturbance on the seabed. Knowledge of the extent and consequences of this disturbance is limited because large‐scale distributions of seabed fauna are not well known. We map faunal distributions in the Australian Exclusive Economic Zone (EEZ) and quantify the proportion of their abundance that occurs in areas 1) that are directly trawled and 2) where legislation permanently prohibits trawling—defined as percentage exposure or protection, respectively. Our approach includes developing a method that integrates data from disparate seabed surveys to spatially expand predicted benthos distributions. Location: Australia. Methods: We collate data from 18 seabed surveys to map the distribution of seabed invertebrates (benthos) in nine regions. Our approach combines data from multiple surveys, groups taxa within taxonomic classes and uses Random Forests to predict spatial abundance distributions of benthos groups from environmental variables. Exposure and protection of benthos groups were quantified by mapping their predicted abundance distributions against the footprint of trawling and legislated boundaries of marine reserves and fishery closures. Results: Trawling is currently prohibited from more area of Australia's EEZ (58%) than is trawled (<5%). Across 134 benthos groups, 96% had greater protection of abundance than exposure. The mean trawl exposure of benthos‐group abundance was 7%, compared to mean protection of 38%, whereas the mean abundance neither trawled nor protected was 55%. Fishery closures covered 19% less study area than marine reserves, but overlapped with a higher proportion (5% more) of benthos‐group abundance. Main Conclusions: This study provides the most extensive quantitative assessment of the current exposure of Australia's benthos to trawling. Further, it highlights the contribution of fishery closures to marine conservation. These results help identify regions and taxa that are at greatest potential risk from trawling and support managers to achieve balance between conservation and sustainable industries in marine ecosystems.